Aplicações bionalíticas do imageamento químico por técnicas de ionização ambiente de espectrometria de massas: DESI e LAESI - Vasconcelos, Géssica Adriana (2020)
Recent advances in mass spectrometry allowed the study of samples with little or no sample preparation. Among these techniques, Desorption Electrospray (DESI) and Laser Electrospray Ionization (LAESI) has gained popularity for their ability to generate chemical images and the use of a laser to study samples under ambient conditions respectively. New DESI users may face several operational problems due to the lack of a literature describing a detailed protocol on how to work with this technique. Although there is a rich literature on DESI, scientific articles always present a brief description of how the experiments were carried out. Thus, the objective of chapter 1 was to present a simple protocol on how to perform imaging experiments by DESIMS. This chapter describes how to optimize the spot, geometric parameters and how to perform an image acquisition. The main application of the DESI imaging technique is in the medical-clinical area. Numerous researchers have investigated the chemical signatures of tumors and cancers for biomarkers that can not only assist on their identification, but also in the development of new treatments for patients. However, there are several clinical areas that have not been much explored by this technology, such as diseases caused by restricted blood flow to the brain. Models of blood flow reduction are often used in mice to simulate stroke that affects humans. Thus, chapter 2 presents the results obtained from the DESI-MS evaluation of the brain of animals after 1, 3 and 7 days after ischemia induction. 2D chemical images were generated for the most abundant ions and PSL-DA statistical analysis was used to verify the most relevant molecular species for this model. Chapter 3 presents the use of LAESI-MS technology in the study of cyanobacteria that commonly produce toxins. The chosen species are known to cause damage to aquatic bodies due to their extensive proliferation in a short period of time. The metabolic profile of each species was investigated, and statistic tools were used to observe the degree of separation between the cyanobacteria species studied. In addition, ion mobility data were used in order to increase molecular coverage and confidence in the identification of species of interest.